Work Domain Analysis Applied to Medical Diagnosis. Issue 1 (June 2014) - Nystrom, Daniel; Williams, Linda; Paull, Douglas; Graber, Mark
Few studies have described the cognitive components that characterize the diagnostic process. This article illustrates the use of work domain analysis to create a functional depiction of diagnosis. The resulting abstraction-decomposition space clarifies the medical diagnostician's work domain and provides a glimpse into the fundamental cognitive features of diagnosis. To facilitate comprehension of the abstraction-decomposition space's portrayal of diagnosis, features of a generalized depiction of diagnosis and the abstraction-decomposition space were graphically coded to communicate areas of similarity. Limitations, suggestions for future work, and future applications of this work to reduce diagnostic error are provided.